2007
DOI: 10.1149/1.2401032
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Supported Platinum Nanoparticles Synthesized by Plasma-Chemical Reduction Method for Fuel Cell Applications

Abstract: Carbon supported platinum nanoparticles were synthesized by reducing H 2 PtCl 6 precursor dissolved in water containing carbon powders by a plasma-chemical method. The fast reduction of the precursor was achieved with the help of active hydrogen species generated in the plasma zone contacting the surface of the aqueous solution. The size of the Pt particles supported on the carbon was in the range of 3 to 5 nm with the solution temperature set at 5°C. The performance of the proton exchange membrane fuel cell e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…One approach is the dielectric barrier discharges (DBD), which have received much attention due to their capability to generate large volume uniform plasmas at atmospheric pressure 2, 3. The atmospheric pressure DBD method has been widely used for various applications including material processing,4–6 particularly in the case of surface treatment of polymers,7, 8 biochemical decontamination process,9, 10 and development of energy related technologies 11–14. The ultimate merits of a plasma method should be evaluated by its capability of achieving plasma uniformity, stability and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is the dielectric barrier discharges (DBD), which have received much attention due to their capability to generate large volume uniform plasmas at atmospheric pressure 2, 3. The atmospheric pressure DBD method has been widely used for various applications including material processing,4–6 particularly in the case of surface treatment of polymers,7, 8 biochemical decontamination process,9, 10 and development of energy related technologies 11–14. The ultimate merits of a plasma method should be evaluated by its capability of achieving plasma uniformity, stability and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[172][173][174] Ag, [175] Cu [176,177] and Al [177] nanoparticles, e.g., can be prepared by treating a solution of the corresponding salt in an ionic liquid with a low temperature ionized Ar plasma, which results in electron transfer into the liquid phase (close to the interface) and subsequent reduction of metal cations.…”
Section: Plasma Methodsmentioning
confidence: 99%
“…Controlled production of hydrogen is therefore obtained by buffering the solution at high pH and then using catalysts, belonging to the transition metalbased compounds: among them, metal salts, metal borides, and precursors of metal oxides [10][11][12]. Metal nanoparticles, with large surface area, increase the catalytic activity [13][14][15]. In earlier work [1] it has been shown that CNT paper functionalized with a film of a polymer-derived SiCN can disperse the transition metals deposited on its surface supposedly into a monolayer, thereby increasing the figure-of-merit (FOM), expressed as the rate of hydrogen generation per unit weight of the metal (per unit molar concentration of NaBH 4 ) for the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…They can be correlated to the cluster size of the metal [29,30] the composition of the metal alloys [30][31][32][33][34][35][36][37][38][39] and the interaction between the metals, ligands and substrates [33,39]. The properties of the substrate, such as its electronic conductivity and surface area, can substantially influence the catalytic efficiency (FOM) [13][14][15][35][36][37][38][39][40][41][42]. SiCN/CNT paper combines a very high surface area with electronic conductivity, permitting electron transfer mechanisms between different sites on the catalyst surface for hydrogen generation.…”
Section: Introductionmentioning
confidence: 99%